CAR-T CELL THERAPY FOR CHRONIC LYMPHOCYTIC LEUKEMIA: A PROMISING IMMUNOTHERAPY APPROACH - KHAN , ZA; ABAID , T; KHAN , J; AHMAD , W; USMAN , M; BABAR , A; NAEEM , M (Biological and Clinical Sciences Research Journal, 2024)
Chronic Lymphocytic Leukemia (CLL) is a prevalent hematological malignancy with limited curative options, necessitating innovative and effective therapeutic approaches. Chimeric Antigen Receptor (CAR) T cell therapy has emerged as a transformative treatment modality, leveraging genetically modified T cells for targeted antitumor activity. This study explores the advancements in CAR T cell therapy for CLL, emphasizing its clinical potential, key manufacturing processes, structural design, therapeutic mechanisms, safety considerations, and strategies for optimizing efficacy. A comprehensive analysis of current literature and clinical data was conducted to examine CAR T cell manufacturing processes, including T cell source selection, activation, genetic modification, and expansion. Detailed evaluation of CAR T cell structural components and generational developments provided insights into their design and functionality. Additionally, therapeutic mechanisms, antigen selection strategies, and toxicity management approaches were critically reviewed. Key findings highlight the iterative advancements across four generations of CAR T cells, enhancing their antitumor efficacy, targeting specificity, and safety profile. Optimal target antigen selection and refinement of structural components, such as the ectodomain, transmembrane domain, and endodomain, significantly contributed to improved functionality. While CAR T cell therapy demonstrated robust antitumor activity in CLL, associated toxicities remain a challenge. Ongoing efforts focus on mitigating adverse events and optimizing clinical outcomes. CAR T cell therapy represents a promising paradigm shift in CLL treatment, combining precision targeting with potent antitumor effects. Continued advancements in design, manufacturing, and safety strategies underscore its transformative potential to improve patient outcomes and revolutionize CLL therapeutics. Further clinical trials and research are warranted to fully realize its therapeutic promise.